919 New crazy game "Russian Biker Roulette". (1st September 2016) - Barbieri, S; Omizzolo, L; Mazloum, R El; Previato, S; Ravaioli, C; Vettore, G; Bergamini, M; Snenghi, R; Feltracco, P
Abstract : Background: The spread of different games through the internet and via social networks is becoming a serious health problem that physicians and medical professionals have to deal with, and it is necessary for them to be aware of the risks those behaviours are connected to. Unintentional injuries are the leading cause of morbidity and mortality among child and teens and some Authors reports recommendation regarding safe practices to reduce injuries [1][2]. The "deadly new craze" involving bikers taking turns to cross a busy road without checking for cars is an unsafe practice visible in web videos. Methods: In this study we considered a particular case of bicycle accident related with a game proposed via web: the bike roulette challenge. We developed an appropriate, educational public health training program to understand the current characteristics of unintentional road traffic injury related with web challenges. Results: This case is about a 16 year-old male patient arrived alive to the hospital with thoracic and abdominal trauma. The length of stay was 18 days associated with serious surgical complications. Conclusion: In recent years is commonly possible to find strange, crazy, popular videos, via web with the intention to obtain in young population a good number of "likes". Bike roulette is a particular game described via web and is one of the new cause of trauma. Identifying biker roulette related injury in administrative data collections can be very problematic; the results of this apparently isolated case report can be used to research appropriate procedures and timely referrals of severe adolescent injury related to web games. School appropriate interventions have got the potential to reduce unintentional trauma related to these behaviours.